Training and Discussions on Seasonal Rainfall Forecasts for March- May 2018 in Rwanda and September- December 2017 Verification - Siebert, Asher; Rose, Alison (2018)
This report describes training activities in Kigali, Rwanda, February 2018, led by Dr. Asher Siebert from the International Research Institute for Climate and Society (IRI). The training visit was part of the Rwanda Climate Services for Agriculture project, a four-year initiative (2016-2019) funded by the U.S. Agency for International Development (USAID) that seeks to transform Rwanda’s rural farming communities and national economy through climate services and improved climate risk management. The main objective of the training visit was to collaborate on seasonal rainfall forecasts for MAM 2018 in Rwanda and SOND 2017 verification.